The application of fMRI to basic experiments in acupuncture. - Ueda, Y.
In this article, the changes in the cerebral activation induced by different acupuncture stimuli were studied using functional magnetic resonance imaging (fMRI). The authors studied how the differences in the stimulus points (hand or leg, left or right) would affect cerebral activities and how differences of stimulus content (sense of pain, not getting qi, getting qi) would alter the cerebral response to the stimuli. Four healthy (normal in neurology) adult subjects: three males and one female, 22- to 30-years-old, and all right-handed were studied. Pain stimuli - getting qi with a noninducing oppressing stimulus (without resonance) and getting qi with an inducing oppressing stimulus - were conducted on the yuchi point. For a meridian point stimulus, a getting-qi inducing oppressing stimulus (with resonance) was conducted with a tenderness meter (FP meter). As qi-inducing pressure, 3.3 kg of pressure was conducted on the right yuchi point and 3 kg on the left yuchi point. Then, the right hand had a strong getting-qi feeling from the pollisis bulb to the elbow, and the left hand had a getting-qi feeling on the pollisis bulb. The different stimulus points produced correspondingly different cerebral activation observed in the S1 area. The differences in stimulus content were evident in the cerebral activation response of the central nervous system (S1, superior temporal gyrus, thalamus, gyrus cinguli, parahippocampal gyrus, cerebellum, and insula). Most of all, the S1 activation of a getting-qi stimulus was bilateral and correlated with the sense of getting qi.
Keywords: 22 to 30 year; 3 kg; 3.3 kg; Acupuncture; Central nervous system; Cerebellum; Cerebral activation; Elbow; Functional magnetic resonance imaging; Getting-qi.; Gyrus cinguli; Hand; Healthy adults; Insula; Meridian point stimulus; Not getting qi; Oppressing stimulus; Pain stimuli; Parahippocampal gyrus; Pollisis bulb; Stimulus content; Superior temporal gyrus; Tenderness meter; Thalamus; Yuchi point